Persistence and Transmission Dynamics of Babesia ovis After Imidocarb Dipropionate Treatment: Evaluation via Blood Transfusion and Tick Infestation - Firat, Recep; Ulucesme, Mehmet Can; Eyvaz, Arda; Alatas, Mehmet; Aktas, Munir; Ceylan, Onur; Ozubek, Sezayi (Mdpi, 2025)
Babesia ovis is a significant tick-borne parasite of sheep, capable of causing both acute disease and long-lasting, low-grade infections. Imidocarb dipropionate (IMDP) is commonly used against babesiosis, yet whether it can completely eliminate B. ovis remains uncertain. In this study, we examined whether the parasite persists after treatment and whether such residual infections can still be transmitted. Three sheep were experimentally infected, treated with IMDP once clinical signs appeared, and then monitored for 180 days by microscopy, nested PCR, and iELISA. Fever and microscopic parasitemia resolved soon after treatment, but nPCR intermittently detected parasite DNA for several weeks. By day 180, all treated sheep were negative by nPCR and microscopy, while two still showed detectable antibodies. Blood collected at this time was transfused into na & iuml;ve sheep. Two of the three recipients showed nPCR positivity at scattered time points and later seroconverted while showing no clinical signs. In contrast, Rhipicephalus bursa ticks that fed on the treated donors neither acquired the parasite nor transmitted it to recipients, likely because post-treatment parasitemia remained below the acquisition threshold. Overall, these results indicate that IMDP controls clinical disease but may not fully clear B. ovis, allowing silent transmission through blood despite negative routine tests.
Keywords: Babesia ovis; blood transfusion; imidocarb dipropionate; parasite elimination Rhipicephalus bursa